2021
DOI: 10.1177/1321103x20985314
|View full text |Cite
|
Sign up to set email alerts
|

Free improvisation in choral settings: An ecological perspective

Abstract: This instrumental case study explores and theorizes on the educational potential and value of free collaborative vocal improvisation, a process that enables equal access to music regardless of musical skills. The focus of the article is on the musical activities of an adult choir in Finland that applied tenets from improvisational theatre to facilitate the social and musical processes of free improvisation. This study applies an ecological perspective to understand how improvisation can offer asylum—a physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Free musical improvisation can be enjoyed by anyone willing to try it, because in free improvisation no prior musical experience is required (Bailey, 1993; Wilson & MacDonald, 2012). In group musical improvisation, students can explore musical possibilities and develop a sense of musical agency while creating shared meaning as they listen carefully and respond meaningfully to fellow improvisers (Lange, 2011; Siljamäki, 2021; Wilson & MacDonald, 2012). By facilitating music improvisation activities, teachers can help students cultivate their musical voices and grow as musical meaning-makers.…”
Section: Musical Improvisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Free musical improvisation can be enjoyed by anyone willing to try it, because in free improvisation no prior musical experience is required (Bailey, 1993; Wilson & MacDonald, 2012). In group musical improvisation, students can explore musical possibilities and develop a sense of musical agency while creating shared meaning as they listen carefully and respond meaningfully to fellow improvisers (Lange, 2011; Siljamäki, 2021; Wilson & MacDonald, 2012). By facilitating music improvisation activities, teachers can help students cultivate their musical voices and grow as musical meaning-makers.…”
Section: Musical Improvisationmentioning
confidence: 99%
“…Fear of negative responses from other improvisers or anxiety about what to play can stifle participation and block self-expression (Siljamäki, 2021; Smith, 2014; Willox et al, 2011). Siljamäki (2021) found that singers in a free improvisation choir overcame fear and inhibition by creating a safe musical/social space.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations